1985
DOI: 10.1111/j.1574-6968.1985.tb00885.x
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli relA strains as hosts for amplification of pBR322 plasmid DNA

Abstract: We have proposed that guanosine tetraphosphate produced in Escherichia coli cells subjected to an isoleucine limitation inhibits pBR322 DNA replication [1]. In E. coli reiA which cannot synthesize guanosine tetraphosphate (ppGpp) upon amino acid limitation pBR322 DNA is amplified after arginine starvation. The yield of plasmid DNA amplified either by chloramphenicol (Cm) or by arginine limitation is compared. The plasmid yidd per cell is equal in amino acid-starved cells and in cells treated with Cm. To increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Hecker et al [18] and Reinikainen et al [34] found that plasmid yields were highest after the culture had entered the stationary phase. Heat treatment, which was accompanied by a reduction in feed rate, resulted in a 50% decrease in growth rate for strains at either growth rate, and therefore a heat treatment may mimic a stationary phase for DNA production.…”
Section: Discussionmentioning
confidence: 97%
“…Hecker et al [18] and Reinikainen et al [34] found that plasmid yields were highest after the culture had entered the stationary phase. Heat treatment, which was accompanied by a reduction in feed rate, resulted in a 50% decrease in growth rate for strains at either growth rate, and therefore a heat treatment may mimic a stationary phase for DNA production.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from providing basic information about the mechanisms of regulation of DNA replication, studies on replication of plasmids during stringent and relaxed response led to development of a new method for DNA amplification in vivo (HECKER et al 1985). It was found that appropriate amino acid starvation may be used as a mean of achieving effective amplification of plasmids derived from ColE1, pSClOl and bacteriophage Iz (HECKER et al, 1985SCHROETER et al 1988, RIETHDORF et al 1989, HOFMANN et al 1990HER-MAN et al 1994a, b, c, WQGRZYN, 1995, NEUBAUER et al 1996. Our results indicate that using this method it is possible to achieve significant amplification of plasmids derived from P1, F, R1 and R6K replicons.…”
Section: Discussionmentioning
confidence: 99%
“…Analogous investigations on the stringent control of Bacillus subtilis chromosome replication led to discovery of an interesting general mechanism of replication regulation (SEROR et al 1986, LEVINE et al 1991. Secondly, appropriate amino acid starvation has been reported as an efficient method for in vivo DNA amplification in the case of ColE1, 1, and pSClOl replicons (HECKER et al, 1985, RIETHDORF et al 1989, HOFMANN et al 1990, HER-MAN et al 1994a, b, c, WEGRZYN 1995, NEUBAUER et al 1996. Therefore, we decided to investigate replication of other replicons during stringent and relaxed response in E. coli.…”
mentioning
confidence: 99%
“…Plasmids (the most commonly used vectors in molecular cloning) may be amplified by different methods. Amino acid starvation ofK coii relA strains was proposed as one of methods for amplification of ColEl plasmids (Hecker et al, 1985;Schroeter et al, 1988;Riethdorfet al, 1989;Hofmann et al, 1990). It has been demonstrated that this method may be even more efficient than the commonly used chloramphenicol method (Clewell, 1972;Guzman et al, 1988;Neubauer et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Recently the conditions for h plasmid DNA amplification during the relaxed response have been optimized (Wegrzyn, 1995). This method of plasmid DNA amplification is very simple and extremely cheap (Hecker et al, 1985;Wegrzyn, 1995). Moreover, it was demonstrated that very efficient overexpression of a gene cloned on a plasmid occurs after simple addition of deprived amino acid following plasmid amplification .…”
Section: Introductionmentioning
confidence: 99%